Internationalization of Micro and Small Enterprises in the Information Technology Industry of the Republic of Croatia - Vlatka Bilas; Sanja Franc; Iskra Kvaternjak (Economic Review: Journal of Economics and Business, 2013)
The value of small enterprises from the information technology industry can be found in their intellectual capital; these enterprises developed high value-added products and therefore contribute to the knowledge-based economy. Through the internationalization process enterprises gain long-term growth and sustainability opportunity on the foreign, as well as on the domestic market. Human capital and knowledge represent the basis for growth of the enterprises from the observed industry, especially for software development companies. Nevertheless, decreased demand for the products from the industry in the Republic of Croatia results in domestic information technology experts deciding to internationalize their business. In this paper primary research was carried out among micro and small software development enterprises in the Republic of Croatia, with the purpose of analyzing the characteristics and the level of their internationalization as well as giving the guidelines for further development.
Keywords: F23; M16; 330; micro; small; enterprise; internationalization; information technology